Ring D-Modified and Highly Reduced Angucyclinones From Marine Sediment-Derived Streptomyces sp. - Guo, Lin; Yang, Qiaoli; Wang, Guangfei; Zhang, Shumin; Liu, Ming; Pan, Xiaohong; Pescitelli, Gennaro; Xie, Zeping (Frontiers in Chemistry, 2021)
Angucyclines and angucyclinones represent the largest family of type II PKS-engineered natural products. Chemical analysis of a marine Streptomyces sp. KCB-132 yielded three new members, actetrophenone A (1) and actetrophenols A–B (2–3). Their structures were elucidated by NMR spectroscopy, X-ray crystallography and CD calculations. Actetrophenone A (1) is the first representative of a novel-type angucyclinone bearing a nonaromatic D-ring. Actetrophenol A (2) features a highly reduced and aromatized four-ring system, which is unprecedented for natural products. While (Ra)- and (Sa)-actetrophenol B (3) bear an unprecedented N-acetyltryptamine-substituted tetraphene core skeleton, this is the first report of a pair of atropisomeric isomers in the angucyclinone family. Actetrophenol A (2) exhibits remarkable antibiotic activity, notably including potent activity to multiple resistant Staphylococcus aureus and Enterococcus faecium with MIC values of 4 µg/mL, in contrast, the positive control antimicrobial agent penicillin was inactive up to 32 µg/mL.